Chronic ethanol exposure differentially alters neuronal function in the medial prefrontal cortex and dentate gyrus. (1st March 2021) - Avchalumov, Yosef; Oliver, Robert J.; Trenet, Wulfran; Heyer Osorno, Rocio Erandi; Sibley, Britta D.; Purohit, Dvijen C.; Contet, Candice; Roberto, Marisa; Woodward, John J.; Mandyam, Chitra D.
Abstract: Alterations in the function of prefrontal cortex (PFC) and hippocampus have been implicated in underlying the relapse to alcohol seeking behaviors in humans and animal models of moderate to severe alcohol use disorders (AUD). Here we used chronic intermittent ethanol vapor exposure (CIE), 21d protracted abstinence following CIE (21d AB), and re-exposure to one vapor session during protracted abstinence (re-exposure) to evaluate the effects of chronic ethanol exposure on basal synaptic function, neuronal excitability and expression of key synaptic proteins that play a role in neuronal excitability in the medial PFC (mPFC) and dentate gyrus (DG). CIE consistently enhanced excitability of layer 2/3 pyramidal neurons in the mPFC and granule cell neurons in the DG. In the DG, this effect persisted during 21d AB. Re-exposure did not enhance excitability, suggesting resistance to vapor-induced effects. Analysis of action potential kinetics revealed that altered afterhyperpolarization, rise time and decay time constants are associated with the altered excitability during CIE, 21d AB and re-exposure. Molecular adaptations that may underlie increases in neuronal excitability under these different conditions were identified. Quantitative polymerase chain reaction of large-conductance potassium (BK) channel subunit mRNA in PFC and DG tissue homogenates did not show altered expression patterns of BK subunits. Western blotting demonstrates enhanced phosphorylation of Ca 2 ⁺/calmodulin-dependent protein kinase II (CaMKII), and reduced phosphorylation of glutamate receptor GluN2A/2B subunits. These results suggest a novel relationship between activity of CaMKII and GluN receptors in the mPFC and DG, and neuronal excitability in these brain regions in the context of moderate to severe AUD.